E- Banking Service Quality of Thrift Banks in Nothern Philippines - Aguinaldo, Kathreen; Doca, Babylene; Israel, Ian Dj; Padilla, Shidely Fiazon; Maramag, Fe Rose-Anne; Catacutan, Karen Joy A. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted to determine the assessment of the quality of the e-banking service among thrift banks in Northern Philippines. Data was collected through a questionnaire. A convenience sampling technique was used to select the respondents. The study revealed that the frequency of client’s use of the service in banks played a significant role in their perception of service quality in thrift banks. It was found that online banking has provided excellent service quality in terms of reliability, responsiveness, efficiency, privacy and security, personal need, and site organization, with personal need as the highest, which indicates how thrift banks have prioritized the need of their customers to switch in online banking and incorporated these personal needs as a feature.